Silicon improves root functioning and water management as well as alleviates oxidative stress in oilseed rape under drought conditions - Saja-Garbarz, Diana; Libik-Konieczny, Marta; Janowiak, Franciszek (Frontiers in Plant Science, 2024)
The aim of our study was to examine how silicon regulates water uptake by oilseed rape roots under drought conditions and which components of the antioxidant system take part in alleviating stress-induced ROS generation in the roots. The study analyzed mainly the changes in the roots and also some changes in the leaves of oilseed rape plants, including total silicon content, relative water content, osmotic potential, stomatal conductance, abscisic acid level, the accumulation of BnPIP1, BnPIP2-1-7 and BnTIP1 aquaporins, and the activity of antioxidant enzymes. It was shown that plants growing in well-watered conditions and supplemented with silicon accumulate smaller amounts of this element in the roots and also have higher relative water content in the leaves compared to the control plants. It was demonstrated for the first time that BnTIP1 accumulation in oilseed rape roots is reduced under drought compared to well-watered plants, and that this effect is intensified in plants supplemented with silicon. In addition, it was shown that silicon supplementation of oilseed rape increases catalase activity in the roots, which correlates with their high metabolic activity under drought and ultimately stimulates their growth. It was shown that silicon improves water balance in oilseed rape plants subjected to drought stress, and that an important role in these processes is played by tonoplast aquaporins. In addition, it was demonstrated that silicon reduces oxidative stress in roots under drought conditions by increasing the activity of catalase.